Answer:
2d
Step-by-step explanation:
For any instance equivalent force acting on the body is
![mg-kd= m(d)/(dt)(dx)/(dt)](https://img.qammunity.org/2020/formulas/physics/college/bn2z0ky8v7webg688rladw8v0jc1m8v7ex.png)
Where
m is the mass of the object
k is the force constant of the spring
d is the extension in the spring
and
d/dt(dx/dt)= is the acceleration of the object
solving the above equation we get
![x= Asin\omega t +d](https://img.qammunity.org/2020/formulas/physics/college/wpufh98airt05o76w55qhisd0ilm7xaxl9.png)
where
![\omega= \sqrt{(k)/(m) } = (2\pi)/(T)](https://img.qammunity.org/2020/formulas/physics/college/42lzoxpygakvvunfz480s7uon3mahbo01n.png)
A is the amplitude of oscillation from the mean position.
k= spring constant , T= time period
Here we are assuming that at t=T/4
x= 0 since, no extension in the spring
then
A=- d
Hence
x=- d sin wt + d
now, x is maximum when sin wt=- 1
Therefore,
x(maximum)=2d